"You are too ethnic, you are too national": Dual identity denial and dual identification. (March 2021) - Cárdenas, Diana; Verkuyten, Maykel; Fleischmann, Fenella
Abstract: Ethnic minorities tend to develop dual identities and therefore can face identity denials from two groups. We examine in two studies the relation between dual identity and experiences of dual identity denial as misgivings or a manifested mistrust of one's group membership from both majority and minority group members. Based on identity integration and threat literature, identity denial represents a threat to dual identity which means that stronger dual identity denial can be expected to be associated with lower dual identity (a negative association). In contrast, based on identity enactment literature, stronger expression of one's dual identity can be expected to elicit stronger identity denial (a positive association). These two contrasting hypotheses were examined in two studies (Study 1 = 474; Study 2 = 820) among ethnic minorities in the Netherlands. The results from both studies offer greater support for the identity enactment model and illustrate the complexities associated with having a dual identity.